Application of multidisciplinary collaborative nursing intervention based on King’s Goal Attainment Theory in medical transition readiness of adolescents with chronic kidney disease - Lili Jia; Shuo Bai; Jiwei Qi; Rong Chen; Maomao Lv; Xiaohui Xu (Frontiers in Pediatrics, 2026)
Objective To explore the application effect of multidisciplinary collaborative nursing intervention based on King's Goal Attainment Theory on medical transition readiness in adolescents with chronic kidney disease (CKD). Methods A total of 88 adolescents aged 15–18 years with CKD admitted to the Department of Pediatrics of a tertiary Grade A hospital from April 2025 to September 2025 were selected. Participants were randomly divided into control group and intervention group using a random number table, with 44 cases in each group. The control group received routine pediatric nursing, while the intervention group received additional nursing intervention for medical transition readiness based on King’s Goal Attainment Theory combined with multidisciplinary team (MDT) collaboration. The intention to participate in health care, self-management ability, and medical transition readiness were compared between the two groups before intervention and 6 months after intervention. Results After 6 months of intervention, the total score of intention to participate in health care in the intervention group (139.18 ± 20.84) was significantly higher than that in the control group (136.74 ± 21.92), with a statistically significant difference (*t* = 3.064, P = 0.005). The total score of self-management and medical transition readiness in the intervention group (60.41 ± 10.85) was significantly higher than that in the control group (58.25 ± 11.61), also with a statistically significant difference (*t* = 2.799, P = 0.01). Scores in all dimensions of the intervention group were significantly higher than those of the control group (all P < 0.05). Conclusion Multidisciplinary collaborative nursing intervention based on King’s Goal Attainment Theory can effectively improve the intention to participate in health care, self-management ability, and medical transition readiness in adolescents with CKD, demonstrating clinical application value.